Can stem bromelain, a pineapple waste product, be used as a drug alternative? A mechanistic insight into protein–protein interactions. (29th October 2020) - Khatun, Samima; Sindhu, Anamika; Venkatesu, Pannuru
Abstract : Binding of stem bromelain to bovine serum albumin induced conformational changes, as shown by various biophysical techniques. Abstract : Stem bromelain (SB) is a mixture of cysteine protease and non-protease components that is extracted from the pineapple plant ( Ananas comosus ). It has several therapeutic applications, such as antithrombotic, anti-inflammatory and anticancer. It also relieves osteoarthritis, diarrhea and various cardiovascular disorders. Bovine serum albumin (BSA), a blood plasma protein, is used as a model transport protein for studying protein folding and ligand binding mechanisms. We investigated the interactions between SB and BSA using UV-visible, fluorescence, isothermal titration calorimetry (ITC), circular dichroism (CD) and Fourier transform infrared (FTIR) techniques. The fluorescence results indicate that the fluorescence intensity of native BSA was quenched with increasing concentration of SB, with a blue shift in its wavelength maxima. The binding constant ( K b ) was found to be on the order of 10 6, which is greater than that of protein–drug interactions; this reflects that SB can be used as an alternative to drugs in treating various diseases. The thermodynamic parameters obtained from isothermal titration calorimetry suggest that hydrophobic interactions play a major role in the association process, and it is an entropically driven process. The CD and FTIR spectroscopic results confirmed conformational alteration in BSA in the presence of SB, which was further substantiated by dynamic light scattering (DLS). The DLS results showed that the hydrodynamic diameter ( d H ) of BSA increases due to interaction with SB, resulting in unfolding of the native structure of BSA. This study is expected to provide important insight into the binding mechanism of SB with BSA, which may be useful in the pharmacology and clinical medicinal fields.